Performance improvement in polymeric thin film transistors using chemically modified both silver bottom contacts and dielectric surfaces - 谢应涛 欧阳世宏 王东平 朱大龙 许鑫 谭特 方汉铿 (Chinese physics B, 2015)
An efficient interface modification is introduced to improve the performance of polymeric thin film transistors. This efficient interface modification is first achieved by 4-fluorothiophenol（4-FTP） self-assembled monolayers（SAM） to chemically treat the silver source–drain（S/D） contacts while the silicon oxide（SiO2） dielectric interface is further primed by either hexamethyldisilazane（HMDS） or octyltrichlorosilane（OTS-C8）. Results show that contact resistance is the dominant factor that limits the field effect mobility of the PTDPPTFT4 transistors. With proper surface modification applied to both the dielectric surface and the bottom contacts, the field effect mobilities of the bottom-gate bottom-contact PTDPPTFT4 transistors were significantly improved from 0.15 cm^2·V^-1·s^-1 to 0.91 cm^2·V^-1·s^-1.